Influence of Worklife Balance on Employee Performance Through Job Satisfaction as an Intervening Variable (Study of CV Pujasani Boyolali Employees) - Putri, Marhaeni Widias; Sugiarto, Agus (Universitas Pamulang, 2024)
This research aims to determine the relationship between each variable involved in the research. These variables are the Worklife-balance, Satisfaction and Employee Performance variables. The main discussion of all these variables will refer to the relationship between the work-life balance variable and employee performance through job satisfaction as an intervening variable. A good work-life balance implemented by an employee can allegedly influence the employee's level of performance. However, this research wants to know the role of other variables, namely the job satisfaction variable as an intermediary variable in this relationship. This research will use a quantitative approach by collecting data through a survey in the form of a questionnaire distributed to respondents. In this research, the respondents involved were employees at CV Pujasani Boyolali. The sample involved in this research involved all employees. The results of this research show that the work-life balance that has been implemented by employees has a significant influence on employee job satisfaction, the work-life balance variable has no influence on employee performance, the job satisfaction variable has no influence on employee performance and the employee job satisfaction variable is unable to influence the state of the relationship between worklife balance variable on employee performance. The practical implications of this research include the development of more proportional human resource management strategies in improving employee performance by paying attention to personal aspects such as work-life balance and job satisfaction of the employee.